Analysis of Profitability Ratio in Predicting Profit Changes in PT. Bank Rakyat Indonesia (Persero) Tbk - Hardianti Hardianti; Agung Widhi Kurniawan; Anwar Anwar; Chalid Imran Musa (Economos : Jurnal Ekonomi dan Bisnis, 2022)
Bank Rakyat Indonesia (Persero) Tbk is one of the largest banks in Indonesia. This study aims to determine and identify the ability of the profitability ratio in predicting profit changes at PT Bank Rakyat Indonesia (Persero) Tbk. ROA, ROE, and NPM are rations used to measure the ability to predict profit changes in this study. The data collection technique used is documentation. The population in the financial statements of PT Bank Rakyat Indonesia (Persero) Tbk., and the sample is PT Bank Rakyat Indonesia (Persero) Tbk., reports for 8 (eight) years calculated quarterly. The results of the research had tested classical assumptions such as normality assumption, multicollinearity assumption, heteroscedasticity assumption and autocorrelation assumption. By applying multiple linear regression techniques in the process of data analysis. The results showed that partially Return on Assets (ROA) was significantly unable to predict profit changes, Return on Equity (ROE) was significantly able to predict profit changes, and Net Profit Margin (NPM) was significantly able to predict profit changes. Simultaneously, Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) was significantly able to predict profit changes.